2018 Vegetable Production Handbook Chapter 17: Sweet Corn Production - Monica Ozores-Hampton; Ramdas Kanissery; Eugene J. McAvoy; Richard N. Raid; Julien Beuzelin (EDIS)
This 16-page fact sheet is chapter 17 of the 2018 Vegetable Production Handbook. Written by Monica Ozores-Hampton, Ramdas Kanissery, Eugene J. McAvoy, Richard N. Raid, and Julien Beuzelin, and published by the Horticultural Sciences Department, 2018.